Implications of the triple track strategy policy on poverty alleviation - Astuti, Susi (Asian Management and Business Review, 2021)
This study aims to analyze the effect of the People's Business Credit, health expenditure, education expenditure, regional investment, and the number of workers on poverty alleviation from the implications of the triple track strategy policy on district/city governments in Central Java Province. This study uses secondary data from 2017 to 2019. The hypothesis testing in this study uses multiple regression analysis through the SPSS 23 program. The results of the test of the coefficient of determination (R2) obtained an Adjusted R Squared of 89%, which indicates that poverty is influenced by variables through the People's Business Credit, health spending, education spending, regional investment, and the number of workers. The results of the study partially show that education spending and regional investment have no effect on poverty alleviation, but the People's Business Credit, health spending, and the number of workers have an effect on poverty alleviation in district/city governments in Central Java Province.